FACTORS INFLUENCING TEENAGE PREGNANCY AMONG ADOLESCENTS ATTENDING ADOLESCENTS' CLINIC AT KALISIZO GENERAL HOSPITAL, KYOTERA DISTRICT IN UGANDA. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Javiira Tebaggwa Baale (Student's Journal of Health Research Africa, 2023)
Introduction: